China’s Internationalization of Higher Education: The Barrier Within - Yang, Rui (International Higher Education, 2020)
China’s achievement in, and approach to, internationalizing its higher education depends greatly on its cultural traits. Historically, Chinese culture has long excelled in incorporating elements from outside its borders, but has fallen relatively behind in reaching out to others. Such a disposition has left deep marks on the ways in which Chinese higher education interacts with the rest of the world.